O ensino de física na escola Estadual de Ensino Médio de Belterra: um olhar para a percepção dos estudantes - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2025)
This study analyzes the perception of high school students from the public school system in Belterra, Pará, regarding the teaching of Physics, identifying their interest in the subject, the main difficulties they face, and suggestions for improving classes. The theoretical framework was built upon the work of authors such as Libâneo, Moreira, and Nardi, and addressed topics such as the historical overview of physics education, methodological obstacles, and more contextualized and accessible didactic alternatives for the local reality. Although the qualitative approach is predominant, the use of questionnaires with closed-ended questions and the numerical treatment of data—such as the total number of student respondents and the percentage of participation—indicate the complementary presence of quantitative elements. Students' open-ended responses were analyzed using a qualitative content analysis, identifying recurring themes. To support this interpretation, a word cloud was used, which visually highlighted the most frequently mentioned terms, facilitating the understanding of students' perceptions. This allows the study to be characterized as having a mixed-methods approach, giving it greater validity and analytical depth. The collected data revealed that the lack of practical classes, the excessive use of technical language, and the difficulty with mathematical content appear as the main obstacles in the teaching of Physics. In conclusion, overcoming these difficulties requires investment in more dynamic and interactive teaching practices, valuing the continuous training of teachers, and using simple, more accessible resources capable of bringing teaching closer to the reality of students in the Amazon.
Keywords: Ensino; Física; Ensino Médio; Educação na Amazônia; CNPQ::CIÊNCIAS HUMANAS